PENYULUHAN KESEHATAN TENTANG DEMAM TIFOID DI SMP NEGERI 26 BANDAR LAMPUNG - Usastiawaty Cik Ayu Saadiah Isnainy; M. Arifki Zainaro (Universitas Malahayati Lampung, 2018)
ABSTRACT The World Health Organization (WHO) estimates the number of cases of typhoid fever in worldwide, reaching 16-33 million with 500-600 thousand deaths in each year. Typhoid fever is an infectious infection that can occur in children and adults. Children are the most susceptible to typhoid fever, although the symptoms experienced by children are lighter than adults. In almost all endemic areas, the incidence of typhoid fever occurs mostly in children aged 5-19 years. The goal after counseling is expected to increase students' knowledge of SMP Negeri 26 Bandar Lampung about typhoid disease. The activities carried out in the form of counseling using leaflets and flipcharts. There was an increase in knowledge of students in Bandar Lampung Junior High School 26 against typhoid disease and ways of prevention and treatment. Thus, giving counseling to students about the prevention and treatment of typhoid fever is very effective. Keywords: Typhoid, Students, Counseling